RATIONALE FOR RESEARCH DATABASE DYNAMIC PROCESSES IN CUTTING - M. R. Guseynova; R. V. Guseinov (Вестник Дагестанского государственного технического университета: Технические науки)
The calculation of the basic parameters of the system for the study of the dynamics of the cutting process.